Physiotherapy management of chemotherapy-induced peripheral neuropathy in Pretoria, South Africa - Esther A. Niemand; Maria E. Cochrane; Carina A. Eksteen (AOSIS, 2020)
Background: The increase in newly diagnosed patients with cancer in South Africa and globally, may contribute to the increase in patients living with chemotherapy-induced peripheral neuropathy (CIPN). Chemotherapy-induced peripheral neuropathy negatively impacts on quality of life (QoL) during and post chemotherapy treatment. Physiotherapy management of CIPN helps patients to manage symptoms and improves function in activity- and participation-levels to ultimately improve QoL. However, little evidence exists regarding the type or combination of physiotherapy management strategies in South Africa. Objectives: The purpose of our study was to determine how the symptoms of CIPN were managed by physiotherapists in Pretoria, South Africa. Method: A quantitative, descriptive study design was used. Electronic questionnaires were distributed to physiotherapists who worked with cancer patients and who treated patients with CIPN. Results: Physiotherapists used massage, proprioceptive neuromuscular facilitation, sensory integration, activities of daily living training, postural drainage, lifestyle modifications; Bobath-, breathing-, stability-, stretching-, strengthening- and endurance-exercises; electrical stimulation, thermal modalities, transcutaneous electrical nerve stimulation, soft tissue mobilisation; muscle energy-, positional- and Mulligan-techniques in the management of CIPN. Conclusion: Cardiopulmonary therapy, therapeutic exercises, manual therapy and neuro-developmental techniques were used by physiotherapists in the management of CIPN. Almost half of the participants did not use electrotherapy techniques. Physiotherapy management strategies that are used in Pretoria are similar to published research. Clinical implications: Physiotherapists in Pretoria are managing CIPN according to international practices. However, studies to determine the effectiveness of the management strategies in a South African context should be conducted. Alternative management strategies, based on the pathophysiology of CIPN, should be explored.